Science, (anti-)communism and diplomacy the Pugwash Conferences on Science and World Affairs in the early Cold War - Kraft, Alison; Sachse, Carola 1951- (Brill, 2020)
"From 1957 onwards, the "Pugwash Conferences" brought together elite scientists from across ideological and political divides to work towards disarmament. Through a series of national case studies - Austria, China, Czechoslovakia, East and West Germany, the US and USSR - this volume offers a critical reassessment of the development and work of "Pugwash" nationally, internationally, and as a transnational forum for Track II diplomacy. This major new collection reveals the difficulties that Pugwash scientists encountered as they sought to reach across the blocs, create a channel for East-West dialogue and realize the project's founding aim of influencing state actors. Uniquely, the book affords a sense of the contingent and contested process by which the network-like organization took shape around the conferences. Contributors are Gordon Barrett, Matthew Evangelista, Silke Fengler, Alison Kraft, Fabian Lüscher, Doubravka Olšáková, Geoffrey Roberts, Paul Rubinson, and Carola Sachse."
Literaturangaben
"Both editors wish to thank our contributors for taking part in a panel at the conference of the European Society for the History of Science in Prague in 2016 and for their cooperation in bringing this collected volume together." -- Acknowledgements
Keywords: Pugwash Conference on Science and World Affairs; Geschichte 1955-1965; Ost-West-Konflikt; Pugwash Conferences on Science & World Affairs; Cold War / History; Nuclear disarmament; Konferenzschrift -- 2016 -- Prag